Neural innervation as a potential trigger of morphological color change and sexual dimorphism in cichlid fish - Liang, Yipeng (Sci Rep, 2020)
Many species change their coloration during ontogeny or even as adults. Color change hereby often serves as sexual or status signal. The cellular and subcellular changes that drive color change and how they are orchestrated have been barely understood, but a deeper knowledge of the underlying processes is important to our understanding of how such plastic changes develop and evolve. Here we studied the color change of the Malawi golden cichlid (Melanchromis auratus). Females and subordinate males of this species are yellow and white with two prominent black stripes (yellow morph; female and non-breeding male coloration), while dominant males change their color and completely invert this pattern with the yellow and white regions becoming black, and the black stripes becoming white to iridescent blue (dark morph; male breeding coloration). A comparison of the two morphs reveals that substantial changes across multiple levels of biological organization underlie this polyphenism. These include changes in pigment cell (chromatophore) number, intracellular dispersal of pigments, and tilting of reflective platelets (iridosomes) within iridophores. At the transcriptional level, we find differences in pigmentation gene expression between these two color morphs but, surprisingly, 80% of the genes overexpressed in the dark morph relate to neuronal processes including synapse formation. Nerve fiber staining confirms that scales of the dark morph are indeed innervated by 1.3 to 2 times more axonal fibers. Our results might suggest an instructive role of nervous innervation orchestrating the complex cellular and ultrastructural changes that drive the morphological color change of this cichlid species.